Peran Ekstrak Kunyit dan Pegagan dalam Modifikasi Ekspresi Gen eNOS: Implikasi Terhadap Gangguan Ginjal pada Obesitas - Agus Sulaeman; Eci Perayani; Soni Muhsinin; Nita Selifiana; Elis Susilawati; Marita Kaniawati; Aghnia Nurvianti Nafilah; Hendra Mahakam; Putra Putra (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Obesity is a global health problem closely associated with endothelial dysfunction, oxidative stress, and renal impairment, where endothelial nitric oxide synthase (eNOS) expression and nitric oxide (NO) levels serve as critical biomarkers for endothelial function. This study aimed to evaluate the effects of turmeric (Curcuma longa) extract, pegagan (Centella asiatica) extract, and their combination on body weight, organ index, fat index, blood biomarkers, and renal eNOS gene expression in obese rats. Male white rats were randomly divided into six groups: normal control, negative control (high-fat diet), positive control (orlistat 10.8 mg/kgBW), turmeric extract (200 mg/kgBW), pegagan extract (200 mg/kgBW), and a combination of turmeric–pegagan extracts (200:100 mg/kgBW). Treatments were administered for 60 days, and parameters assessed included body weight, organ index, fat index, blood biomarkers (ITT, creatinine, NO, elastin), and renal eNOS expression using PCR. Statistical analysis was performed using one-way ANOVA followed by Tukey’s post hoc test. The results demonstrated that the combination of turmeric and pegagan extracts significantly reduced body weight, liver, kidney, and heart indices, as well as visceral fat index, while improving blood biomarkers through the reduction of creatinine levels, along with an increase in NO serum approaching normal compared with the negative control group; the respective mean values were -10.14±0.57%, 5.52±0.73%, 1.23±0.21%, 0.64±0.06%, 1.35±0.05%, 0.33±0.06 mg/dL, dan 5.14±0.58 mmol/L. Renal eNOS expression exhibited an increasing trend in the combination group, although not statistically significant. In conclusion, the combination of turmeric and pegagan extracts exerts synergistic effects in improving endothelial dysfunction and renal impairment in obesity through lipid profile modulation, reduction of organ damage biomarkers, and enhancement of NO bioavailability.